2011
DOI: 10.1093/jxb/err394
|View full text |Cite
|
Sign up to set email alerts
|

Plant organellar calcium signalling: an emerging field

Abstract: This review provides a comprehensive overview of the established and emerging roles that organelles play in calcium signalling. The function of calcium as a secondary messenger in signal transduction networks is well documented in all eukaryotic organisms, but so far existing reviews have hardly addressed the role of organelles in calcium signalling, except for the nucleus. Therefore, a brief overview on the main calcium stores in plants-the vacuole, the endoplasmic reticulum, and the apoplast-is provided and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
270
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(274 citation statements)
references
References 215 publications
(255 reference statements)
4
270
0
Order By: Relevance
“…S7, B and C) showed that these two elements were colocated in the vacuoles (Fig. 3B), thereby ensuring low cytoplasmic concentrations of Ca (Stael et al, 2012) and Mn (Hughes and Williams, 1988;Peiter et al, 2007). This suggests that narrow-leafed lupin is able to translocate Mn(II) from the apoplast for storage in the vacuole, possibly via a Ca transporter (Millaleo et al, 2010), limiting the accumulation of Mn in the cytoplasm and cell wall.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…S7, B and C) showed that these two elements were colocated in the vacuoles (Fig. 3B), thereby ensuring low cytoplasmic concentrations of Ca (Stael et al, 2012) and Mn (Hughes and Williams, 1988;Peiter et al, 2007). This suggests that narrow-leafed lupin is able to translocate Mn(II) from the apoplast for storage in the vacuole, possibly via a Ca transporter (Millaleo et al, 2010), limiting the accumulation of Mn in the cytoplasm and cell wall.…”
Section: Discussionmentioning
confidence: 93%
“…m-XRF analysis indicated that Ca was located mostly in the vacuoles (Supplemental Fig. S6B), which Stael et al (2012) concluded contain approximately 80 mM Ca compared with only approximately 100 nM in the cytoplasm. The concentration of Mn must be maintained at less than 100 nM in the cytoplasm also (Hughes and Williams, 1988), but in contrast to Ca, there was low Mn in the vacuoles but high in some intervening spaces ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently become evident that plastids represent a significant pool for Ca 2+ release in plants (21,37,38). We measured hyperosmotic-induced Ca 2+ responses in plastidial-localized kea mutant lines.…”
Section: Survey Of Ion Transporters That May Play a Role In Elicitingmentioning
confidence: 99%
“…levels fluctuate and they are in rapid control of membrane-localized Ca 2? pumps and channels located in plasmalemma, vacuoles and endoplasmic reticulum of plants (Stael et al 2011;Ng and Mcainsh 2003;Yang and Poovaiah 2003). Therefore, it is anticipated that due to the small size, high surface area-tovolume ratio and continuum in flux, nanoscale calcium oxide particles could be transported with ease through ionic channels in the plant system and also we imagine that the relatively high electrochemical potential energy of the nanoscale materials also plays an important role in phloem transport of calcium oxide nanoparticles.…”
Section: Leavesmentioning
confidence: 99%